(untitled) - Brooks, Myrna LaFleur (St. Louis, 2005)
This bestselling text provides students with the basic knowledge of medical language they need to communicate clearly with other health care team members. It presents not only medical terms built from word parts, but also those not built from word parts - which are sometimes omitted from other texts. Logically organized with a body system approach, this text also provides a brief review of anatomic terminology. A wealth of exercises helps students memorize word parts and their meanings, so they'll be equipped to recognize and define new medical terms
Keywords: Medicine,Dược phẩm; terminilogy,programmed instruction,Thuật ngữ,Hướng dẫn lập trình